The Potential Impact of Entrepreneurship Education on Doctoral Students Within the Non-Commercial Research Environment in Chile - Muñoz-Canales, C; Guerra-Velasquez, M (Routledge, 2020)
Chilean doctoral programs in science and technology generally do not consider entrepreneurial training within their curricula. Taking an entrepreneurial competency approach, we explore the potential impact of introducing an entrepreneurship education course to doctoral students based within a non-commercial research environment. We identified two main areas of possible impact: the potential effects upon doctoral research projects and upon the doctoral students themselves. We followed the learning experiences of science and technology PhD students before, during, and a year after an entrepreneurial course through a multiple case study research design. Our results suggest that entrepreneurship education has a positive impact upon the development of student’s creative problem-solving and communication skills. This was reported to have a generally positive effect upon the students’ doctoral projects and on the student’s self-efficacy and entrepreneurial intentions. We conclude that entrepreneurship education complements traditional doctoral training for students within a non-commercial academic setting. © 2019, © 2019 Society for Research into Higher Education.